Sistem Pelayanan Badan Penyelenggara Jaminan Sosial Kesehatan Di Rumah Sakit Islam Faisal Makassar - Dianpungkassari, Dianpungkassari; Usman, Jaelan; Haerana, Haerana (Universitas Muhammadiyah Makassar, 2021)
The purpose of this study was to find out the patient service satisfaction with the system services of the Social Security Administering Bodies (BPJS) health at Islamic Hospital Faisal Makassar. This study used qualitative research. The number of informants in this study were 4 people using in-depth interview techniquq. This study used primary and secondary data, these two types of data were obtained by observation, interviews and documentation. Data analysis used data reduction techniques, presentation of data and conclusions. Based on the results of direct interviews and data analysis showed that the indicators achievement of patient service satisfaction as seen from accountability, transparency, participation, conditionality, and equal rights had worked quite well, but they must be addressed especially in the accountability process for drug distribution against patients at the Islamic Hospital Faisal Makassar. This study showed patient service satisfaction greatly affects the results of the agency service system Health Social Security (BPJS) organizer at the Islamci Hospital Faisal Makassar. Keywords: BPJS Health, Service System